Theoretical overview of clinical and pharmacological aspects of the use of etelcalcetide in diabetic patients undergoing hemodialysis - Ye J; Deng G; Gao F (Dove Medical Press, 2018)
Jianzhen Ye,1 Guangrui Deng,1 Feng Gao2 1Department of Endocrinology, Huangzhou District People’s Hospital, Huanggang, People’s Republic of China; 2Department of Endocrinology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China Abstract: Etelcalcetide is the first intravenous calcimimetic agent authorized for the treatment of secondary hyperparathyroidism (sHPT) in patients undergoing hemodialysis in Europe, the US, and Japan. The relationship between sHPT and diabetes resides on complex, bidirectional effects and largely unknown homeostatic mechanisms. Although 30% or more patients with end-stage renal disease are diabetics and about the same percentage of those patients suffer from sHPT associated with hemodialysis, no data on the specificities of the use of etelcalcetide in such patients are available yet. Regarding pharmacokinetic interactions, etelcalcetide may compete with oral hypoglycemics recommended for use in patients undergoing hemodialysis and insulins detemir and degludec, causing unexpected hypocalcemia or hypoglycemia. More importantly, hypocalcemia, a common side effect of etelcalcetide, may cause decompensation of preexisting cardiac insufficiency in diabetic patients or worsen dialysis-related hypotension and lead to hypotension-related cardiac events, such as myocardial ischemia. In diabetic patients, hypocalcemia may lead to dangerous ventricular arrhythmias, as both insulin-related hypoglycemia and hemodialysis prolong QT interval. Patients with diabetes, therefore, should be strictly monitored for hypocalcemia and associated effects. Due to an altered parathormone activity in this patient group, plasma calcium should be the preferred indicator of etelcalcetide effects. Until more clinical experience with etelcalcetide is available, the clinicians should be cautious when using this calcimimetic in patients with diabetes. Keywords: glucose intolerance, renal impairment, calcimimetic, type 2 diabetes, hyperparathyroidism, parathyroid hormone